2022
DOI: 10.3389/fcimb.2022.832235
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of Three Commercial SARS‐CoV‐2 Rapid Antigen Tests for Community-Dwelling Individuals in a Tropical Setting

Abstract: During the second year of the COVID-19 pandemic, the use of Rapid Diagnosis Antigen Tests (RDAgTs) for SARS-CoV-2 detection has substantially increased as some of the brands available in the market were certified for clinical use by international regulatory agencies. RDAgTs are a fast and cheap tool for SARS-CoV-2 surveillance with great potential to improve testing capacities in middle- and low-income countries compared to the gold standard RT-qPCR. However, as the clinical performance of RDAgTs has been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Third, this study was conducted using residual specimens stored in VTM as per the manufacturer's recommendation. Previous studies have reported that the sensitivity of Ag-RDTs varied from 11.1% to 98.0% according to the Ag-RDT kit, specimen type, and viral load in the specimen [ [6] , [7] , [8] , [15] , [16] , [17] , [18] , [19] , [20] , 23 ]. The sensitivity was high in NPS specimens with a high viral load, whereas it was significantly low in sputum specimens [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Third, this study was conducted using residual specimens stored in VTM as per the manufacturer's recommendation. Previous studies have reported that the sensitivity of Ag-RDTs varied from 11.1% to 98.0% according to the Ag-RDT kit, specimen type, and viral load in the specimen [ [6] , [7] , [8] , [15] , [16] , [17] , [18] , [19] , [20] , 23 ]. The sensitivity was high in NPS specimens with a high viral load, whereas it was significantly low in sputum specimens [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, rRT-PCR has several disadvantages. It is expensive, requires sophisticated laboratory infrastructure, and depends on skilled laboratory personnel [ [6] , [7] , [8] ]. In addition, the long turnaround time of rRT-PCR could delay a prompt diagnosis of SARS-CoV-2 infection, resulting further transmission [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations